Formula Apportionment and Transfer Pricing under Oligopolistic Competition - Søren Bo Nielsen; Pascalis Raimondos-Møller; Guttorm Schjederup (Copenhagen Business School (CBS), Department of Economics, 2000)
This paper demonstrates that under conditions of imperfect (oligopolistic) competition, a transition from separate accounting (SA) to formula apportionment (FA) does not eliminate the problem of profit shifting via transfer pricing. In particular, if affiliates of a multination firm face oligopolistic competition, it is beneficial for the multinational to manipulate transfer prices for tax-saving as well as strategic reasons under both FA and SA. The analysis shows that a switch from SA rules to FA rules may actually strengthen profit shifting activities by multinationals.
hdl:10398/7654
Keywords: D43; 330; Formula apportionment; Transfer pricing; Oligopolistic competition